RESILIENSI DAN KEBAHAGIAAN DENGAN SOMATISASI PADA MAHASISWA TINGKAT AKHIR - Pujiarohman, Pujiarohman; Astuti, Indah Ayu Kusuma; Muslimah, Alfiana Indah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
This study aims to determine the level of somatization, resilience and happiness, to find out there is a significant relationship between resilience and happiness with somatization, and to find out there is a significant effect between resilience and happiness with somatization in finalyear students at the Islamic University "45" Bekasi. This research is a correlational quantitative research. The research subjects are final year students at the Islamic University "45" Bekasi. The number of samples is 88 people. Sampling is done by means of stratified random sampling Data collection methods in this study were interviews and psychological measurement scales. The research instrument used was the resilience scale (CD-RISC), the Happiness scale, and the somatization scale using the Likert model and the Adult Somatization Inventory (ASI). The data was obtained using a Likert scaleand processed using SPSS version 21.0. The reliability test using Cronbach's Alpha resulted inan r Alpha value = 0.949 for resilience, an r Alpha value = 0.838 for happiness, an r Alpha value = 0.963 for somatization. Data analysis using Pearson Product Moment Correlation and Multiple Linear Regression methods. The results of the analysis show that there is a negative relationship between resilience and somatization, the correlation coefficient value is -0.226 with a p-value of 0.034 (p<0.05). The results of the analysis for the second correlation are thatthere is a negative relationship between happiness and somatization, the correlation coefficientvalue is -0.230 with a p-value of 0.031 (p<0.05). These results indicate that the research hypothesis is accepted. The results of the multiple regression test between resilience (β1 = - 0.240, = 0.049 <0.05) and happiness (β2 = -0.545, = 0.028 <0.05) on somatization from the study showed that resilience had a negative and significant effect on somatization and happiness have a negative and significant influence on somatization. That is, 9.7% of resilience and happiness are influenced by these factors. While 90.3% is influenced by other variables not examined in this study.